Experimental Investigation of Thermal Modal Characteristics for a Ship’s Foundation under 300°C - Zheyu Ding; Hongbai Bai; Yiwan Wu; Yue Zhu; Yichuan Shao (Shock and Vibration)
How to further reduce vibration and noise is a major challenge for modern ship design. High-temperature environment will significantly influence the mechanical properties (such as elastic modulus and stiffness) of the ship’s foundation. These properties will have a serious impact on the inherent vibration characteristics of the foundation. In this paper, a simplified foundation is taken as the research object, and a thermal-vibration joint test system is developed for investigating the thermal modal characteristics of the foundation under different temperatures. The joint test system consists of a transient aerodynamic heating environment simulation system and a vibration excitation and acquisition system. Finite element method (FEM) is used to analyze the distribution of thermal fields. The influence of the ceramic rods and the different ambient temperatures on the modal characteristics of the foundation is studied. The results indicate that the effect of ceramic rods on the modal characteristic of the foundation is negligible. The results also show that the greater the vibration response amplitude is as the temperature increases and the first-order natural frequency does not change, the smaller the second-order natural frequency and the damping ratio will become smaller. The variation of natural frequency and damping ratio of the foundation under different temperature conditions can provide a reliable experimental basis for the design of the vibration and noise reduction of the ship’s foundation in the thermal-vibration environment.